Productive Fandom Intermediality and Affective Reception in Fan Cultures - Lamerichs, Nicolle; Project Muse; Project Muse. (Project Muse, 2020)
To dismantle negative stereotypes of fans, this book offers a media ethnography of the digital culture, conventions, and urban spaces associated with fandoms, arguing that fandom is an area of productive, creative, and subversive value. By examining the fandoms of Sherlock, Glee, Firefly, and other popular television-based franchises, the author appeals to fans and scholars alike in her empirically grounded methodology and insightful analysis of production hierarchies, gender, sexuality, play, and affect.
Shared narratives : intermediality in fandom -- Fan membership : traditional and digital fieldwork -- Naturalizing Sherlock : Dutch fans interpret the famous -- Queer teen drama : rewriting and narrative closure in Glee -- Transmedia play : approaching the possible worlds of Firefly -- Embodied characters : the affective process of cosplay -- Conclusion : prospects for fan studies.
Issued as part of book collections on Project MUSE.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Fans (Persons) -- Social aspects; Television programs -- Social aspects; Television viewers -- Social aspects; Electronic books; Electronic books